Poor Reading Culture among Teens in Public Schools: Role of Location Variable - Obiyo, Ngozi; Ihunnia, Gabriel (International Journal of Psychosocial Rehabilitation, 2024)
The study determined poor reading culture among teens in public schools in Nigeria and the role oflocation variable. It made use of a descriptive survey design. A total of 400 teens, including those with specialneeds participated in the study. Three objectives served as a guide to the study. A questionnaire was used toelicit information from the respondents. It was found that poor reading culture has consequences that usuallymanifest in the academic and overall life of teens. Results also showed no significant difference in the meanratings of urban and rural teens’ location on the consequences and remedies of poor reading culture. Finally,the menace of poor reading culture can be remedied by good teaching skills, a conducive teaching and learningenvironment, making reading materials available and affordable, among others. Among the recommendationsmade are establishing well-equipped libraries, including a subject called ‘Reading Culture’ in the curriculum,subsidizing the costs of reading material, establishing standard reading competitions, and handsome rewardsfor winners, and creating an inclusive environment to cater for those with special needs